(untitled) (Ameghiniana, 2013)
Several in complete skeletons of juvenile Prosauropoda and two eggs were recovered from Upper Triassic beds of Southern Patagonia. The specimens are refered to a new genus and species, Mussaurus patagonicus, showing a mixed picture of anatomical affinities. Fore lirnbs, pelvis and hind limb are tipically Prosauropoda; the short cervical vertebrae resemble those of the Middle Triassic thecodont Lagosuchus, and some characters of the skull suggest relationships with both Prosauropoda and Sauropoda. Tentatively a new family of Prosauropoda is proposed to include this new species.